PEMBELAJARAN BERBASIS PANCASILA DALAM ETIKA TRANSAKSI DIGITAL: ANALISIS PEMANFAATAN PEMBAYARAN DIGITAL MAHASISWA - Auvia, Sirrul; Amalia, Trisilia Deta; Karina; Abdillah, Aditya; Farenda, Baiq Nila; Febriana, Baiq Susanti; Herianto, Edy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study explores the integration of Pancasila values in students' digital transaction ethics through the use of QRIS in the FKIP Universitas Mataram canteen. With a qualitative phenomenological approach, this study collected data through observation and in-depth interviews. The results show that the use of QRIS provides convenience, efficiency, and security in digital transactions. However, obstacles such as unstable internet networks and QR code damage still occur. This study confirms that learning based on Pancasila values, such as justice, mutual-cooperation, responsibility, and transparency, plays an important role in shaping students' transaction ethics. The integration of these values encourages students to transact wisely, prevent consumptive behavior, and build a sustainable and ethical digital ecosystem. Education plays a strategic role in ensuring that students are not only technologically proficient but also have high moral awareness and social responsibility. Thus, the implementation of QRIS in the campus environment is an effective means of instilling character based on Pancasila in the digital era. Keywords: Learning, Pancasila values, digital ethics.